EFFICACY OF Cordyceps fumosorosea AND Silico-Sec® AGAINST STORED PRODUCT PESTS: IMPACT ON MORTALITY, FECUNDITY, MYCOSIS, AND SPORULATION - Muhamad Yasin; Waqas Wakil; Mirza Abdul Qayyum; Misbah Ashraf; Abdulrahman S. Aldawood; Mubasher Hussain; Hafiz Muhammad Bilal Yousuf; Areej Mahfooz (Journal of Animal and Plant Sciences, 2026)
Stored grain insect pests threaten global food security by reducing the quality and quantity of grain, highlighting the urgent need for sustainable and eco-friendly alternatives to chemical insecticides. In current laboratory tests, entomopathogenic fungi,Cordyceps fumosorosea, and a diatomaceous earth (DE) formulation, Silico-Sec®, were tested against the adult stages of Liposcelis paeta, Cryptolestes ferrugineus, Rhyzopertha dominica, and Tribolium castaneum using a completely randomized design (CRD) with three replications.Diatomaceous earth was applied at a concentration of 200 ppm, while C. fumosorosea was introduced at 1×10⁶ and 1×10⁸ conidia kg-1 of wheat, either individually or in integrated manners. After 21 days of exposure, the highest mortality in all insect species was observed in T1 (L. paeta: 69.53%, C. ferrugineus: 56.76%, R. dominica: 51.58%, and T. castaneum: 43.90%), followed by T3 and T2 in individual treatments. In combined treatments, T5 resulted in the highest mortality (L. paeta: 100.0%, C. ferrugineus: 95.12%, R. dominica: 92.47%, and T. castaneum: 83.65%). The lowest LT50 and LT90 values were recorded for L. paeta, indicating their higher susceptibility, while the T. castaneum exhibited the highest resistance towards all the treatments. Maximum progeny emergence was recorded in T2 (L. paeta: 44.33%; C. ferrugineus: 49.44%; R. dominica: 54.88%; and T. castaneum: 61.44%) compared to the control treatment. On the other hand, the highest mycosis (T2: 87.21%; T3: 77.32%; T4: 55.20%; and T5: 41.10%) and sporogenesis (T2: 185.22; T3: 167.67; T4: 152.22; and T5: 140.67 spores) were recorded in L. paeta. The results indicated that C. fumosorosea and Silico-Sec® can be used as effective grain protectants and provide significant control when used alone or in combination against major storage insect pests. Their exceptional mode of action qualifies them as an efficient and viable solution, reflecting their importance as critical aspects in IPM interventions in the preservation of stored grains.
Keywords: Cordyceps fumosorosea; Silico-Sec®; Progeny emergence; Mycosis; Sporogenesis